1994
DOI: 10.1044/0161-1461.2503.136
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Emerging Literacy in a Language Preschool

Abstract: Preschool children with speech and language impairments (SLI) are at significant risk for later literacy learning difficulties. Current emerging literacy theory dictates the inclusion of reading and writing in preschool programs for children with SLI. Early literacy interactions are directed at developing all modes of communication and providing normalizing experiences for children with SLI. In addition, these experiences may lessen future academic learning problems. The purpose of this article is to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Emergent literacy interventions for young at-risk children are generally framed within the theoretical perspective that emergent literacy knowledge is best acquired through frequent, informal, naturalistic, and meaningful interactions with literacy-related artifacts (e.g., books, writing instruments; Watkins & Bunce, 1996;Watson, Layton, Pierce, & Abraham, 1994). Mediated interaction with such artifacts under the guidance of more capable and knowledgeable individuals (e.g., parents, teachers, siblings, friends) is a primary vehicle through which children acquire increasingly sophisticated levels of emergent literacy knowledge (Justice & Ezell, 1999).…”
Section: Emergent Literacy Intervention: Current Perspectivesmentioning
confidence: 99%
“…Emergent literacy interventions for young at-risk children are generally framed within the theoretical perspective that emergent literacy knowledge is best acquired through frequent, informal, naturalistic, and meaningful interactions with literacy-related artifacts (e.g., books, writing instruments; Watkins & Bunce, 1996;Watson, Layton, Pierce, & Abraham, 1994). Mediated interaction with such artifacts under the guidance of more capable and knowledgeable individuals (e.g., parents, teachers, siblings, friends) is a primary vehicle through which children acquire increasingly sophisticated levels of emergent literacy knowledge (Justice & Ezell, 1999).…”
Section: Emergent Literacy Intervention: Current Perspectivesmentioning
confidence: 99%
“…This particular story centers on preschoolers (boys and girls) participating in an ethnically mixed preschool classroom that includes appropriate elements (see Watson, Layton, Pierce, & Abraham, 1994). The narrative retelling and dictation task is designed to assess several elements of emergent literacy development.…”
Section: Narrative Assessment Using the Wordless Picture Bookmentioning
confidence: 99%
“…A literate society is one in which reading and writing are important aspects of everyday life. Therefore, we typically think of a literate individual as one who is able to read and write (Watson, Layton, Pierce & Abraham, 1994). However, the term "literate language" has an even broader meaning.…”
Section: Review Of Literature Literate Languagementioning
confidence: 99%
“…Not only is reading essential to economic and personal success in the long run, but, in the short term reading helps children expand their vocabularies and improve overall language skills (Catts, 1993;Watson et al, 1994). Research also has shown that children who spend time reading perform better in school than their peers who read less often (Chard & Dickson, 1999, Catts, 1997).…”
Section: Review Of Literature Literate Languagementioning
confidence: 99%
See 1 more Smart Citation